Extraction and Partial Characterization of a Lipophilic, Fungicidal Molecule Associated with Serum Albumins - Ericson, Brett Richard (Worcester Polytechnic Institute, 2007)
Vulvovaginal candidiasis (VVC) is a mucosal infection caused by Candida species and represents one of the most common clinical problems in women of reproductive age (68,71). Annually in the United States there are approximately 13 million cases of VVC, resulting in 10 million gynecologic office visits per year (38). It is estimated that 75% of women will experience at least one episode in their lifetime, with a projected 50% of all women experiencing multiple episodes (23). Candida albicans is a dimorphic commensal organism of the urogenital and gastrointestinal tracts and has been identified as the main pathogenic agent in VVC, accounting for approximately 85-90% of patients with positive cultures (52). Despite extensive research, the invasive mechanism of vaginal yeast infections is not well understood. Traditionally it has been assumed that changes in the host vaginal environment promote the dimorphic transition from blastospore to hyphae, resulting in a shift from asymptomatic colonization to symptomatic vaginitis (28). In contrast to the normal, systemic immune response, which confers an aseptic environment for tissue and organs, immune responses at the mucosal level are designed to prevent tissue invasion and local disease while maintaining an indigenous flora that could be both beneficial and pathogenic (28). Since fungi are eukaryotic, the vital cellular mechanisms that are usually targeted by modern pharmacologic agents, such as DNA replication and protein translation, are either conserved or have a strong homology to their human orthologs. Obtaining a better understanding of natural fungal suppression mechanisms and molecules at the mucosal level may pave the way for the development of more efficacious drugs or preventative regiments. The mechanism by which the human immune system is able to resist fungal invasion at the vaginal mucosa is unknown. Our research was aimed at finding any host factors that might play a role in the suppression of or prevention of a fungal infection at the vaginal mucosa. In order to screen candidate molecules that might be important in this type of vaginal defense, we chose a pathogenic C. albicans strain, SC5314, to test fungal cell viability upon introduction of the candidate molecules. We have identified a host factor that exhibits strong fungicidal activity when organically extracted from both human and bovine serum albumins. Characterization of this factor through organic extractions and acetone separations reveal that this molecule is a non-polar lipid. Serum samples that have been thoroughly stripped of fatty acids and other lipophilic molecules show no apparent fungicidal activity in cell viability assays. Since the factor is extractable from both human and bovine serum albumins, it may be conserved among mammals. Identification and characterization of this molecule may play a pivotal role in understanding host-Candida interactions at the mucosal membrane interface. Due to its human origin, the use of this factor as an antifungal would be extremely advantageous in regards to FDA (Food and Drug Administration) guidelines and ADMET (Adsorption, Distribution, Metabolism, Excretion, Toxicology) properties.